2016
DOI: 10.1021/acs.jpcc.6b05737
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Multilayered Plasmonic Nanostars for Coherent Random Lasing

Abstract: Here, we report that hybrid multilayered plasmonic nanostars can be universally used as feedback agents for coherent random lasing in polar or nonpolar solutions containing gain material. We show that silver-enhancement of gold nanostars reduces the pumping threshold for coherent random lasing substantially for both a typical dye (R6G) and a typical fluorescent polymer (MEH-PPV). Further, we reveal that the lasing intensity and pumping threshold of random lasers based on silver-enhanced gold nanostars are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Importantly, their limited cytotoxicity 4 promises to enable their use in vitro and in vivo. However, despite the wealth of applied work 5,6,7 , very limited fundamental research has been carried out on these particles, both from the experimental and theoretical standpoints 8,9,10 . As a result, published research cannot be evaluated comparatively, and, therefore, implemented at the industrial scale for technologically relevant applications.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, their limited cytotoxicity 4 promises to enable their use in vitro and in vivo. However, despite the wealth of applied work 5,6,7 , very limited fundamental research has been carried out on these particles, both from the experimental and theoretical standpoints 8,9,10 . As a result, published research cannot be evaluated comparatively, and, therefore, implemented at the industrial scale for technologically relevant applications.…”
Section: Main Textmentioning
confidence: 99%
“…(6) (7) The absorption and scattering cross sections are defined by the energy rates absorbed and scattered by the nanostar volume and surface area, defined in Equations 8 and 9 respectively, and divided by the incident irradiance, given by Equation 10:…”
Section: )mentioning
confidence: 99%
“…Furthermore, in view of the potential use of nanostars as hot electron‐based photocatalysts, the possibility to isolate the tips from the remainder of the nanostar, thus enabling us to prove their role as source of hot electrons, could lead to interesting fundamental studies on the generation and fate of these hot carriers. While protocols exist to coat nanostars with silica, and silica coated nanostars have found wide range applicability, unfortunately, no established protocols exist to selectively coat the nanostar core while leaving the tips exposed. In addition, known protocols for silica etching would be too aggressive for the delicate nanostar morphology and would lead to tip reshaping …”
Section: Figurementioning
confidence: 99%
“…Hrelescu. et al reported that hybrid multilayered plasmonic nanostars can reduce the pumping threshold for random lasing [ 20 ]. Follow-up demonstrations have motivated researchers to study localized surface plasmon resonance random multimode lasers in polymer thin films doped with gain dye and silver nanoparticles [ 21 ].…”
Section: Introductionmentioning
confidence: 99%